2018
DOI: 10.1007/s10555-018-9752-y
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the COX2/PGE2/EP axis in therapeutic resistance

Abstract: Therapeutic resistance has been and remains to be the major challenge in developing successful treatments for different cancers and therefore, understanding the underlying mechanisms in the development of therapeutic resistance is crucial in combating cancers. Multiple mechanisms underlie the development of therapeutic resistance, and the signaling pathways involved in cancer stem cell repopulation, enhanced epithelial-mesenchymal transition (EMT), inflammatory infiltration, and immunosuppression play pivotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 129 publications
2
62
0
Order By: Relevance
“…Therapeutic Efficacy. Because COX-2 is associated with tumor promotion and therapeutic resistance (54,55), we hypothesized that targeting COX-2 activity would inhibit the ability of ruxolitinib-treated macrophages to promote resistance of TNBC cells to ruxolitinib. Celecoxib effectively reduced the PGE2 production by ruxolitinib-treated human primary macrophages (Fig.…”
Section: Celecoxib In Combination With Ruxolitinib Leads To Enhancedmentioning
confidence: 99%
“…Therapeutic Efficacy. Because COX-2 is associated with tumor promotion and therapeutic resistance (54,55), we hypothesized that targeting COX-2 activity would inhibit the ability of ruxolitinib-treated macrophages to promote resistance of TNBC cells to ruxolitinib. Celecoxib effectively reduced the PGE2 production by ruxolitinib-treated human primary macrophages (Fig.…”
Section: Celecoxib In Combination With Ruxolitinib Leads To Enhancedmentioning
confidence: 99%
“…In parallel, the COX2/PGE2/EP axis appears as a pivotal key not only in tumor initiation and progression but also in the development of therapeutic resistance. 58 Overexpression of COX2 and mPGES-1 (microsomal prostaglandin E synthase) are commonly detected in penile intraepithelial neoplasia and carcinoma. 24 Herein, we demonstrated the genetic mechanism related to the overexpression of COX2 by demonstrating its higher production at mRNA and protein levels.…”
mentioning
confidence: 99%
“…Constitutive COX2 expression is triggered by pathways activated by oncogenic stimuli and cyto-chemokines, such as MAPK, PI3K/AKT and NFkB that are frequently hyperexpressed in most of resistant tumors [ 17 ]. Upregulation of the COX2/PGE2 axis favors proliferation, angiogenesis, invasion, apoptosis resistance, and the activation of immunosuppressive cells contributing to tumor progression and therapy resistance [ 43 ]. We showed that COX2 and PTGES are both overexpressed in several BRAF/MEKi-resistant melanoma cells and tumor tissues, and that COX2 knockdown significantly enhanced drug effects in melanoma cell.…”
Section: Discussionmentioning
confidence: 99%